What it means to care - J.R. Wilkinson (AOSIS, 1998)
In order to practice an ethic of care within the nursing profession, that is, in order to care for those for whom the nurse is responsible, caring for others needs to be distinguished from merely carrying out one's obligations by following rules. This article by using the method of philosophical analysis argues that caring is an emotion-like state fitting within a general explanation of the emotions as concern based construals and therefore as unified experiences of beliefs, desires and feelings. By clarifying the concept of care, it tries to lay a foundation for inculcating a culture of caring into the practitioners of the caring profession. Since caring involves care-specific beliefs and desires caring requires acquiring the appropriate beliefs and desires which constitute the experience of caring for others.